Health-related quality of life in transgender adolescents: Associations with body image and emotional and behavioral problems. Issue 1 (2nd January 2018) - Röder, Mieke; Barkmann, Claus; Richter-Appelt, Hertha; Schulte-Markwort, Michael; Ravens-Sieberer, Ulrike; Becker, Inga
ABSTRACT: Background : Transgender adolescents who apply for treatment often experience a marked increase in body-related distress when entering puberty, accompanied by internalizing problems and poor peer relations. Although adolescence is a time of considerable psychosocial and physical change, generally associated with a decline in health-related quality of life (HRQoL), research on HRQoL in transgender youth and possible predictors is sparse. This study thus aims to explore the predictive value of body image factors and emotional and behavioral problems for HRQoL. Methods : This cross-sectional one-group observational study was carried out at the Child and Adolescent psychiatric department (Gender Identity Service) in Hamburg, Germany. A sample of n = 126 (103 trans male and 23 trans female) adolescents, who were referred for counseling and/or treatment completed different standardized instruments before undergoing any sort of treatment. Firstly, five dimensions of HRQoL were explored in transgender adolescents and secondly, a linear regression model was applied to assess the impact of body image and emotional and behavioral problems on overall HRQoL. Results : HRQoL was generally impaired in transgender adolescents compared to norm scores, especially with regard to aspects of psychological and physical well-being. Linear regression analysis revealed that greater internalizing problems and less body satisfaction significantly predicted lower HRQoL outcomes. Conclusions : Impaired HRQoL may be explained by high degrees of internalizing problems and low body satisfaction. Thus, one important aim of mental health professionals working with youth should be to provide appropriate treatment and counseling options that may contribute to overall well-being in the long-term.